2015
DOI: 10.1371/journal.pone.0134641
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Narratives in the Age of Misinformation

Abstract: Social media enabled a direct path from producer to consumer of contents changing the way users get informed, debate, and shape their worldviews. Such a disintermediation might weaken consensus on social relevant issues in favor of rumors, mistrust, or conspiracy thinking—e.g., chem-trails inducing global warming, the link between vaccines and autism, or the New World Order conspiracy. Previous studies pointed out that consumers of conspiracy-like content are likely to aggregate in homophile clusters—i.e., ech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 36 publications
3
79
0
3
Order By: Relevance
“…This is consistent with early psychology conceptualisations of belief in conspiracy theories as an ideological trait (Goertzel, 1994). The belief seems to exist as a global phenomenon as it has been found in various kinds of society (Bessi et al, 2015;Swami 2012;Van Prooijen, 2015) and does not exclusively occur in conflict areas such as the Middle East region as explained by Al-Azm (2011) andGray (2010). However, the result showed that religious fundamentalism did not predict a belief in conspiracies, nor did it interact with NFC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is consistent with early psychology conceptualisations of belief in conspiracy theories as an ideological trait (Goertzel, 1994). The belief seems to exist as a global phenomenon as it has been found in various kinds of society (Bessi et al, 2015;Swami 2012;Van Prooijen, 2015) and does not exclusively occur in conflict areas such as the Middle East region as explained by Al-Azm (2011) andGray (2010). However, the result showed that religious fundamentalism did not predict a belief in conspiracies, nor did it interact with NFC.…”
Section: Discussionsupporting
confidence: 86%
“…A corpus analysis of Facebook comments in Italian shows that people are most persistent in commenting on geopolitical conspiracies compared to environment, diet and health issues (Bessi et al, 2015). In Malaysia, belief in a common Jewish conspiracy to exploit Malaysian resources and people was indicated as an attempt to serve ideological needs; it portrayed society's perceived ability to understand threat and to shape socio-political dynamics within (Swami, 2012).…”
Section: Need For Closure and Conspiracy Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…13, beliefs formation and revision is influenced by the way communities attempt to make sense of events or facts. Such a phenomenon is particularly evident on the WWW where users, embedded in homogeneous clusters (14)(15)(16), process information through a shared system of meaning (10,11,17,18) and trigger collective framing of narratives that are often biased toward self-confirmation.…”
mentioning
confidence: 99%
“…Recent works (7) provide empirical evidence of the pivotal role of confirmation bias and selective exposure in online social dynamics. Users, indeed, tend to focus on specific narratives and join polarized groups (i.e., echo chambers) (8)(9)(10), where they end up reinforcing their worldview [even if pieces of content are deliberately false (11,12)] and dismissing contradictory information (13). Discussion and elaboration of narratives in such a segregated environment elicits group polarization and negatively influences user emotion (14-17).…”
mentioning
confidence: 99%